New data on two rare East Asian cladocerans, Coronatella trachystriata (Chen, Zhang & Liu, 1994) and Nedorhynchotalona chiangi Kotov & Sinev, 2011 (Cladocera: Anomopoda: Chydoridae) - Sinev, Artem Y.; Liu, Ping; Han, Bo-Ping (Zootaxa, 2024)
Two rare East Asian cladocerans, Coronatella (Coronatella) trachystriata (Chen, Zhang et Liu, 1994) and Nedorhynchotalona chiangi Kotov & Sinev, 2011, were found in Qili Lake on the border of Anhui and Jiangsu Provinces of China. Morphology of the species was studied by scanning electron microscopy for the first time, revealing unique morphological features: valve sculpture as a system of ridges in C. (C.) trachystriata and head shield with only lateral head pores present in N. chiangi. Both species have numerous adaptations for a benthic mode of life. They were found in a pelagic plankton sample during strong wind action, but were absent in littoral samples. Our data suggest that both species inhabit bottom sediments in a deeper zone of lakes at some distance from the shore, usually not sampled during cladoceran faunistic surveys. Morphology and distribution of the species are discussed.